Feeding Ecology of Nilgiri Langur (Trachypithecus johnii) in Silent Valley National Park, Kerala, India - Ramachandran, K. K.; Joseph, Gigi K. (Indian Forester, 2001)
Feeding ecology of Nilgiri Langur has been studied in the rainforest ecosystem of Silent Valley from 1993 to 1996. Eighty-nine food species were identified through direct observations. A majority of them were typical evergreen species. Monthly and seasonal variations in the percentage frequency of feeding observations on different food items in the diet were observed. The need of conserving the evergreen habitats for the endangered Nilgiri Langur is discussed.